2021
DOI: 10.2147/ijgm.s309003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Low Level of Vitamin D Among COVID-19 Patients and Associated Risk Factors in India – A Hospital-Based Study

Abstract: Background The world is facing the most challenging pandemic in the 21st century. The developed and developing countries are facing the burden equally and no proven treatment options available. Recent studies suggest the plausibility of vitamin D therapy and prophylaxis for COVID-19, in the setting where the deficiency is more prevalent. Though evaluation of vitamin D status is not a routine in India, the present study focuses on the level of Vitamin d among COVID-19 patients. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
0
10
0
8
Order By: Relevance
“…However, it is important to note that the combined effect of all variants that tend to lower 25D levels is only about 5% [ 121 ]. Further, a hospital-based cross-sectional investigation in India observed a prevalence of 59% and 89% of vitamin D deficiency and insufficiency, respectively, among 156 COVID-19 hospitalized patients [ 122 ].…”
Section: Recent Clinical Data Assessing An Association Between Vitamin D and Covid-19 Infection And Course Of Diseasementioning
confidence: 99%
“…However, it is important to note that the combined effect of all variants that tend to lower 25D levels is only about 5% [ 121 ]. Further, a hospital-based cross-sectional investigation in India observed a prevalence of 59% and 89% of vitamin D deficiency and insufficiency, respectively, among 156 COVID-19 hospitalized patients [ 122 ].…”
Section: Recent Clinical Data Assessing An Association Between Vitamin D and Covid-19 Infection And Course Of Diseasementioning
confidence: 99%
“…Data from other studies show a consistent relationship between older age and more severe disease. 16 , 20 , 22 , 24 , 25 , 26 Our data showed a median age of 52 years in the symptomatic group versus 39 years in the asymptomatic group. Higher BMI has been identified as a risk factor for severe disease or poor outcomes such as the need for invasive ventilation or death.…”
Section: Discussionmentioning
confidence: 50%
“…Using the same definition of vitamin D deficiency and insufficiency as our study, a study performed in India found similar results to our study with a combined prevalence of vitamin D deficiency (< 20 ng/mL) and insufficiency (20 ng/mL – 30 ng/mL) at 89.1%. 16 This comprised 58.9% of vitamin D deficient patients and 30.2% with vitamin D insufficiency. Likewise, an Algerian study found a prevalence of vitamin D insufficiency (20 ng/mL – 30 ng/mL) and deficiency (< 20 ng/mL) of 75.1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This point has incited studies to investigate the effect of an imperfect or lower level of Vitamin D, linking it with many other severe health conditions like autoimmune disorders, cardiovascular disease (CVD), hypertension (HTN), and other diseases. Similarly, various studies have been conducted on the positive benefits of Vitamin D on the early recovery and prevention of COVID-19 [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%